Stability and Control During Vertical Take-Off and Landing: The Impact of Aerodynamics - Tudorel-Petronel Afilipoae; Pedro Simplicio; Samir Bennani; Hans Strauch (Aerospace)
Under the European Space Agency (ESA) support, INCAS has taken the initiative to develop an Ascent and Descent Autonomous Maneuverable Platform (ADAMP) which will serve as an in-flight testing platform for reusable space technologies. This paper is focusing on activities aimed at assessing the robustness of the control system of the ADAMP in the presence of aerodynamic disturbances, with an emphasis on stability and disturbance rejection. Considering the ADAMP’s inherent aerodynamic instability, the way aerodynamic forces and moments are incorporated in the control design formulation plays a critical role in the effectiveness of the adopted control solution in the presence of wind gusts and potential interaction with sloshing modes. To showcase these phenomena, two alternative control design methodologies are employed in the paper: the baseline strategy relies on robust self-scheduled structured H-Infinity optimization, while the second approach is based on nonlinear sliding mode theory. Different structured H-Infinity controllers are designed and analyzed in the frequency domain, providing a clear understanding of the impact of the aerodynamic effects in terms of stability margin degradation. These controllers are then thoroughly compared with the sliding mode alternative via nonlinear worst-case simulation of typical ascent and descent flights in the presence of strong wind gusts.